Aging, cognition, and the brain: effects of age-related variation in white matter integrity on neuropsychological function. (3rd July 2019) - Fan, Yang-Teng; Fang, Ya-Wen; Chen, Ya-Ping; Leshikar, Eric D.; Lin, Ching-Po; Tzeng, Ovid J.L.; Huang, Hsu-Wen; Huang, Chih-Mao
ABSTRACT: Alterations in brain structure are viewed as neurobiological indicators which are closely tied to cognitive changes in healthy human aging. The current study used diffusion tensor imaging (DTI) tractography to investigate the relationship between age, brain variation in white matter (WM) integrity, and cognitive function. Sixteen younger adults (aged 20–28 years) and 18 healthy older adults (aged 60–75 years) underwent DTI scanning and a standardized battery of neuropsychological measures. Behaviorally, older adults exhibited poorer performance on multiple cognitive measures compared to younger adults. At the neural level, the effects of aging on theWM integrity were evident within interhemispheric (the anterior portion of corpus callosum) and transverse (the right uncinate fasciculus) fibers of the frontal regions, and the cingulum-angular fibers. Our correlation results showed that age-related WM differentially influenced cognitive function, with increased fractional anisotropy values in both the anterior corpus callosum and the right cingulum/angular fibers positively correlated with performance on the visuospatial task in older adults. Moreover, mediation analysis further revealed that the WM tract integrity of the frontal interhemspheric fibers was a significant mediator of age–visuospatial performance relation in older adults, but not in younger adults. These findings support the vulnerability of the frontal WM fibers to normal aging and push forward our understanding of cognitive aging by providing a more integrative view of the neural basis of linkages among aging, cognition, and brain.